Effect of silicon dopant on mechanical properties of monolayer graphene. Issue 1 (June 2020) - Majeti, V K; Roy, A; Gupta, K K; Dey, S
Abstract: The exceptional qualities of graphene have drawn the attention of many researchers and scientists. It has exhaustive real-life applications, ranging from mechanical and medical domain to electronic fields. The significant properties of graphene can be tailored by chemical functionalization methods. By incorporating foreign atoms, the properties of pristine graphene can be modified. Molecular dynamics (MD) simulations are carried out to conduct tensile tests on square-shaped graphene doped by silicon. The fracture strength, failure strain and Young's modulus are measured on grapheme doped by silicon. The carbon atoms in the graphene sheet are replaced randomly with silicon atoms for this simulation and the variation of mechanical properties are observed by comparing with the pristine form of graphene. The properties such as Young's modulus, fracture strength and failure strain are found to reduce with the increase of doping intensity. During chemical vapour deposition (CVD) method as silicon atoms are likely to replace the carbon atoms, it may promote the electronic properties but in the present study, it is found to decline its mechanical properties due to increase in silicon doping concentration. As a result, it is therefore suggested to consider the effect of silicon dopants in the applications of graphene.